A note on "Necessary and sufficient conditions for the perfect finite horizon folk theorem" [Econometrica, 63 (2): 425-430, 1995.] - Ghislain H. Demeze-Jouatsa (Bielefeld University, Center for Mathematical Economics (IMW), 2018)
Smith (1995) presented a necessary and sufficient condition for the finite- horizon perfect folk theorem. In the proof of this result, the author constructed a family of five-phase strategy profiles to approach feasible and individually rational payoff vec- tors of the stage-game. These strategy profiles are not subgame perfect Nash equilibria of the finitely repeated game. I illustrate this fact with a counter-example. However, the characterization of attainable payoff vectors by Smith remains true. I provide an alternative proof.
urn:nbn:de:0070-pub-29303808
Keywords: C72; C73; 330; Finitely Repeated Games; Subgame Perfect Nash Equilibrium; Folk Theorem; Discount Factor